Microorganisms Resistance Pattern and Antibiotic Prescriptions in Patients Admitted to the Intensive Care Unit in Ghazy AL Hariri Hospital (Medico Legal Update, 2021)
Introduction: Resistance to antibiotics has emerged recently due to the misuse of antibiotics and is a threatto the health?care system, especially in developing countries like Iraq where there are no antimicrobialstewardship programs in most intensive care units (ICU).Materials and Method: This was anobservational, cross-sectional study done in the ICU of Ghazi ALHariri hospital, Medical City/Iraq. All patients getting admitted to ICU from both genders were included inthe study.Samples taken for culture and sensitivity tests included blood, urine, tracheostomy tube, sputum,cerebrospinal fluid, central venous line, and bedsore swab.Results: 43 patients satisfied the inclusion and exclusion criteria and were included in the study. The mostcommon isolated pathogens were pseudomonas in sputum and blood samples, Acinetobacter in wounds andoperation skin site infection, Klebsiella in central venous line, and bedsore swab, while Candida in the urine.Klebsiella was the most frequently isolated in overall culture results, it was most sensitive to imipenem,meropenem, and amikacin.Conclusion: Ceftriaxone was the most commonly used antibiotic as an empiric treatment followed bymeropenem and amikacin. Most of the isolated pathogens (> 90%) had resistance to ceftriaxone. ICUacquired Klebsiella, P. aeruginosa, and Acinetobacter predominate hospital-acquired infections.